A blind casting into the evidential sea: the interplay between fundamental rights and the efficacy of leniency programmes - Kollmar, Christy L. (Riga Graduate School of Law, 2018)
This article makes the case that proper protection of Defendants’ fundamental rights, through the enhancement of procedural predictability and increased evidentiary transparency, will lead to more efficient, efficacious and sustainable leniency programmes equating to more fear of violative behaviour detection, an increased acknowledgment of anti-competitive participation, and enhanced overall cartel destabilisation for more balanced competition in the marketplace. With the clear link that exists between the severity of sanctioning, the exploitation of the leniency programme, and the protection of fundamental rights, it becomes imperative that a Defendant’s fundamental rights are not undermined so a later finding of cartel infringement can remain viable under heightened judicial scrutiny. The article provides final recommendations on how to strengthen leniency programmes by and through safeguarding a Defendant’s fundamental rights related to search warrant procurement and execution. The final recommendations provide insight on: Subject Matter and Purpose of the Investigation Burden / Threshold of Proof Procedure on Warrant Execution Obtainment of ‘Follow-on’ Evidence
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Competition law